2014
DOI: 10.3233/jvr-140706
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge translation strategies to improve the resources for rehabilitation counselors to employ best practices in the delivery of vocational rehabilitation services

Abstract: The purpose of this article is to acknowledge the gap between research and practice in vocational rehabilitation (VR) and provide strategies for VR counselors to help bridge that gap. Evidence-based practice (EBP) and knowledge translation (KT) are two concepts that help the implementation of research into practice and have been adopted in health care and other related fields for many years. Although most research supports the implementation of these theories in health care settings, it is a fairly new concept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Underscoring this theme were the experiences of the authors who also acted as Pre-ETS facilitators and instructors as part of the study. As detailed in Lau & McKelvey (2023), research staff discuss the importance of their role as facilitators to initiate Pre-ETS. Despite educators' and VR eagerness, access to students, space, time, and resources were often limiting factors that had to be overcome.…”
Section: Family Engagement and Interagency Collaborationmentioning
confidence: 99%
See 1 more Smart Citation
“…Underscoring this theme were the experiences of the authors who also acted as Pre-ETS facilitators and instructors as part of the study. As detailed in Lau & McKelvey (2023), research staff discuss the importance of their role as facilitators to initiate Pre-ETS. Despite educators' and VR eagerness, access to students, space, time, and resources were often limiting factors that had to be overcome.…”
Section: Family Engagement and Interagency Collaborationmentioning
confidence: 99%
“…Often, the modifications were done to make the concept of work less abstract and connect employment terms to conduct expected in school. As described in Lau & McKelvey (2023), making connections to specific student interests was vital to successful instruction. However, instructional autonomy also underscores the authors' previous point that professional training differs between educators and VR counselors.…”
Section: Instructional Autonomy and Technologymentioning
confidence: 99%
“…The current research also examined whether the extent to which counselors read and use peer-reviewed publications were associated with several factors (Anderson, Matthews, Lui, & Nierenhausen, in press; Lui, Anderson, Matthews, Nierenhausen, & Schlegelmilch, 2014; Murray, 2009). We conceptualized factors that may be associated with counselors’ reading and using of peer-reviewed publications existing at different levels: organizational factors (e.g., supervisors, organizational culture, caseload demands), professional identity (e.g., professional organization affiliation, professional’s perceptions of their professional role), and individual counselors’ judgments or opinions of peer-reviewed publications.…”
Section: Factors Affecting Counselors’ Reading and Using Peer-reviewementioning
confidence: 99%
“…First, research has demonstrated that rehabilitation counselors employed in work environments in which they have easy access to evidenced-based information and workplaces that encourage applying evidenced-based practices are more likely to implement evidenced-based practices (e.g., Anderson et al, in press; Graham et al, 2013; Lui et al, 2014). In the same vein, we reasoned that work environments have the potential to affect counselors’ use of peer-reviewed publications.…”
Section: Factors Affecting Counselors’ Reading and Using Peer-reviewementioning
confidence: 99%
“…Mechanisms put in place by a unified governance model to encourage research programs in areas unique to the rehabilitation counseling profession that develops its EBP would be valuable in achieving this outcome. Further, knowledge translation strategies are needed to ensure rehabilitation counselors adequately respond to the evidence base and provide individuals with disabilities and their families the best practices and therefore the best opportunities for successful rehabilitation outcomes(Lui, Anderson, Matthews, Nierenhausen, & Schlegelmilch, 2014;Sherman, Del Valle, Chan, Landon & Leahy, 2018). The profession's governance needs to play a key role in promoting the translation of EBPs through up-to-date professional development activities for members, and to students through rigorous accreditation and reciprocal partnerships with university rehabilitation counseling programs.…”
mentioning
confidence: 99%